THE FINANCIAL PERFORMANCE AND MACROECONOMIC FACTORS IN FORMING STOCK RETURN - Bertuah, Eka; Sakti, Indra (Jurnal Riset Manajemen dan Bisnis (JRMB) Fakultas Ekonomi UNIAT, 2019)
This research focuses on fundamental and macroeconomic conditions in the formation of stock returns as an empirical test on signaling theory, capital structure theory, and prospect theory. The research sample is companies listed on the BEI property sector with a total of 17 companies that meet the criteria of purposive sampling. The analysis technique uses panel data regression with random effects. The results showed simultaneously that financial performance and macroeconomic factors affect stock returns. The partial test shows that profitability and capital structure do not affect stock returns, while PBV and macroeconomic factors have a positive effect on stock returns. In addition, GDP is the dominant factor affecting stock returns. The implications of this study refer to investors in determining investment strategies, for management in managing companies and for regulators in making economic policy decisions. Keywords: Stock Return, Financial Performance, Macroeconomic, Property Sector